2021
DOI: 10.1177/13524585211003479
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of T1w/T2w ratio in patients with multiple sclerosis from first clinical presentation

Abstract: Background: Cross-sectional studies suggest normal appearing white matter (NAWM) integrity loss may lead to cortical atrophy in late-stage relapsing-remitting multiple sclerosis (MS). Objective: To investigate the relationship between NAWM integrity and cortical thickness from first clinical presentation longitudinally. Methods: NAWM integrity and cortical thickness were assessed with 3T magnetic resonance imaging (MRI) in 102 patients with clinically isolated syndrome or early MS (33.2 (20.1–60.1) years old, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…In the NAWM, compared with HC, T1w/T2w ratio was significantly lower already from mild disability levels and in patients with RRMS and SPMS, but not in those with CIS and PPMS. Although in contrast with some previous reports,11 16 our results in patients with RRMS are consistent with other studies,12–14 18 showing no significant differences in the early phases of the disease but only in patients with a longer disease duration. Discrepancies among studies may be explained by heterogeneities in the cohorts of patients with MS investigated, often with small sample sizes and short disease duration, and in the methods applied to quantify T1w/T2w ratio.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the NAWM, compared with HC, T1w/T2w ratio was significantly lower already from mild disability levels and in patients with RRMS and SPMS, but not in those with CIS and PPMS. Although in contrast with some previous reports,11 16 our results in patients with RRMS are consistent with other studies,12–14 18 showing no significant differences in the early phases of the disease but only in patients with a longer disease duration. Discrepancies among studies may be explained by heterogeneities in the cohorts of patients with MS investigated, often with small sample sizes and short disease duration, and in the methods applied to quantify T1w/T2w ratio.…”
Section: Discussionsupporting
confidence: 83%
“…T1w/T2w ratio values were found significantly lower in the NAWM of early relapsing-remitting (RR) MS compared with healthy controls (HC) 12 14 18. However, this was not confirmed in other studies where no difference was detected in patients with MS compared with HC 11 13 16. Some studies found a significantly lower cortical T1w/T2w ratio in patients with RRMS and progressive MS,6 17 but not in the early phases of the disease 16.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, another work did not show any significant associations between T1-w/T2-w and EDSS, although the sample size was much smaller (26 patients) ( Granberg et al, 20172017 ). A recent longitudinal work ( Cooper et al, 2021 ) in CIS and early MS patients showed that T1-w/T2-w in NAWM is associated with increasing lesion volume and disease activity in the first 2 years of disease after first clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Preprocessing included white and grey matter brain masking 13 for brain extraction, N4-bias field correction 14 and linear, rigid body registration of FLAIR images to MPRAGE images. 15 MPRAGE and FLAIR scans were longitudinally co-registered as described in Cooper et al 16 Cerebral Gd- and T2-hyperintense lesions were segmented manually and saved as binary masks using ITK-SNAP ( www.itksnap.org ) by two expert MRI technicians (greater than 10 years of experience). Longitudinally co-registered MPRAGEs were lesion-filled ( https://fsl.fmrib.ox.ac.uk/fsl/fslwiki/lesion_filling ) and used for whole brain, white and grey matter and CSF normalised volume extraction.…”
Section: Methodsmentioning
confidence: 99%